Randomized Controlled Trial of a Novel Cementless vs. Cemented Total Knee Arthroplasty: Early Clinical and Radiographic Outcomes - Enze Zhao; Xiaoyan Zhu; Haiwei Tang; Zhenyu Luo; Weinan Zeng; Zongke Zhou (Orthopaedic Surgery)
Objective Previous cementless total knee arthroplasty (TKA) designs faced challenges with insufficient initial fixation on tibial side, resulting in inferior functional outcomes and survival rates. The Zoned Trabecular Bone Cementless Knee is a novel implant designed for cementless TKA which aims to achieve excellent initial fixation, promoting effective osseointegration. The aim of this research was to compare the early clinical and radiographic results of this cementless TKA with cemented TKA. Methods Between September 2021 and April 2022, 64 patients (64 knees) were recruited in this prospective randomized controlled trial to receive either cementless 3D‐printed trabecular metal TKA or a cemented posterior stabilized TKA. Preoperative and postoperative clinical evaluations, including the range of motion (ROM), Knee Society Score (KSS), and the Reduced Western Ontario and MacMaster Universities Score (WOMAC), were conducted and analyzed for comparison. Radiographs and computed tomography scans were utilized to assess the initial fixation. The complications between the two groups were also recorded and compared. Continuous data were analyzed for significance using independent‐samples t‐test or the Mann–Whitney U test and categorical data were analyzed using chi‐squared or Fisher's exact test. Results Both groups demonstrated significant enhancement at 12 months follow‐up in the ROM compared with baseline (ROM: 94.7 ± 23.4 vs. 113.1 ± 12.3 in cementless group and 96.5 ± 14.7 vs. 111.0 ± 12.8 in cemented group, p < 0.05). However, no statistical differences were observed between the two groups in postoperative ROM, KSS, or WOMAC score. The radiographs and computed tomography scans showed similar results, including radiolucent lines and osteolysis in either femoral or tibial. Additionally, there was no statistical difference in the overall complication rate between the two groups. Notably, one patient in the cementless TKA group required revision for periprosthetic infection as the end point. Conclusions This novel 3D‐printed trabecular metal cementless TKA achieved comparable clinical outcomes and initial fixation to cemented TKA in early stage. Longer‐term examination is necessary to validate these results.